GREEN BUDGETING AS A NEW TOOL OF SUSTAINABLE DEVELOPMENT AND THE PRACTICE OF ITS APPLICATION IN UZBEKISTAN - Ismailova Nasiba Komildjanovna (American Journals, 2024)
In this article, the transition to a green economy in order to ensure the stability of the economy, prevention of climate change, inclusive economic growth, the use of budget and fiscal policy tools to achieve environmental goals and the transition to green budgeting practice in Uzbekistan, the advantages of green budgeting, and the issues that exist during the transition to this practice are highlighted. Given.
Keywords: Economic stability, inclusive growth, renewable energy, public finance, budget policy, environmental budget, public sector entities, public budget funds, green economy, green budgeting, green bonds.